The bacterial community of the chicken's intestinal tract: impact of xylanase supplement - Samsudin, Anjas Asmara @ Ab Hadi; Al-Hassani, Dihya Hassan (Universiti Putra Malaysia Press, 2014)
The effect of xylanase supplementation on the profile of the bacterial community of the gastrointestinal tract of layer chicken was investigated using PCR-DGGE analysis. Thirty four common bands, belonging to Lactobacillus acidophilus and Lactobacillus salivarius, were excised from the DGGE gel, amplified, cloned and sequenced. Sequence analysis of the clones revealed that 79.4% of sequences from the intestine were related to those of Lactobacillus spp., while the remaining 20.6% belonged to the four families, Clostridiaceae (8.8%), Streptococcus (5.8%), Bacteroides (3%) and Enterococcus (3%). Bacteria belonging to the genus Lactobacillus spp. were the predominant bacteria across the different treatments and segments of the gastrointestinal tract of chicken.